Stunting Among Children Aged 6-59 Months in Gorontalo, Indonesia - Sri Nurlaily Z; Rahma Dewi Agustini; Nurhidayah (Jurnal Kesehatan Masyarakat, 2025)
Stunting remains a significant public health challenge in Indonesia, particularly among children aged 6-59 months. Stunting, defined as low height-for-age, results from chronic undernutrition during the most critical periods of growth and development. This study aims to analyze the sociodemographic and socio-cultural factors associated with stunting in Gorontalo, Indonesia, to inform targeted interventions. A cross-sectional study was conducted with 325 children aged 6-59 months, selected consecutively. Data were collected using a structured questionnaire covering seven sociodemographic and two sociocultural factors, alongside the Individual Dietary Diversity Score (IDDS) questionnaire. Bivariate analysis was performed using Chi-Square tests, while multivariate analysis employed Logistic Regression to identify significant predictors of stunting. The prevalence of stunting among the sample was 35.7%. Bivariate analysis identified Birth Length, Birth Weight, Family Income, Exclusive Breastfeeding, Complementary Foods, Food Diversity, and Parenting as factors associated with stunting. Multivariate analysis revealed that Birth Length (OR=0.377; 95% CI: 0.188-0.754), Birth Weight (OR=0.231; 95% CI: 0.095-0.561), Exclusive Breastfeeding (OR=0.307; 95% CI: 0.164-0.575), and Food Diversity (OR=0.064; 95% CI: 0.033-0.123) were significant protective factors against stunting. Conversely, Family Income and Education were identified as confounding factors. The findings underscore the critical importance of the first 1000 days of life in preventing stunting. Efforts should improve maternal nutrition to ensure optimal birth weight and length, promote exclusive breastfeeding, and enhance dietary diversity among young children. Addressing these factors can significantly reduce the prevalence of stunting and improve child health outcomes in Gorontalo.